Monitoring of the poly-professional competence development in the project activity of students - Katushonok I.Yu, Sofina V.N, Murashev A.V., Gabova M.P., Polezhaeva O.D., (Opción, 2019)
The article considers the features of poly-professional competence development in the project activities of high school students via comparative qualitative research methods. A comparative analysis of the professional qualities of students of two groups (1st and 4th-year undergraduate) showed that most of the professional qualities’ components of 1st-year students are less developed than those of 4th-year students and image-result (graduates). In conclusion, with greater involvement of students in project activities such as skills as effective oral communications, quality and result orientation, a creative approach to solving problems, responsibility, interpersonal communication, performing discipline, open-mindedness, are formed.